The Journey of a Successful Ex-Offender: A Case Study - Barbara E. Varner; Irene C. Baird (Adult Education Research Conference, 2014)
Consider that adult education has turned its focus on transformative learning and is considered a framework for both research and practice; the purpose of this study was to explore transformative learning and to consider whether it is applicable and/or relevant to the experiences of a successful ex-offender, Jonathan Queen.